PSEUDOMORPHISM OF WEDDELLITE IN UROLITHS - Katkova V.I.; Rakin V.I.; Makeev B.A. (My University, 2007)
The crystals of calcium oxalate attract attention because of their wide abundance in different human organs and tissues (urinoexcretory pathways, teeth, bones, mammary glands, and others). Calcium oxalate in uroliths occurs in two (dihydrate and monohydrate) crystalline forms. It is important to study the crystal genesis and transformation of oxalates, because no reliable methods of their nonsurgical removal from the human organism have been found as yet. The crystals of calcium oxalate monohydrates CaC2O4 * H2O (whewellite) are colorless, orthorhombic, and monoclinic. The space group is P21/n , Z = 8, with unit cell parameters a0 = 6.290 Å, b0 = 14.583 Å, c0 = 10.116 Å, and β = 109.46° [13]. In nature, whewellite mainly occurs in sedimentary rocks that contain syngenetic or migration organic matter.